P0046ZHX2 DOWNREGULATION DUE INSERTIONS AND DELETIONS IN THE HAS2-ZHX2 INTERGENIC REGION PREDISPOSE TO PODOCYTE DISEASE RELAPSE. (6th June 2020) - Del Nogal Avila, Maria; Das, Ranjan; Kharlyngdoh, Joubert; Molina Jijon, Eduardo; Donoro Blazquez, Hector; Gambut, Stephanie; Crowley, Michael; Crossman, David; Gbadagesin, Rasheed A; Nagel, Stefan; Avila Casado, Carmen; Clement, Lionel; et al.
Abstract: Background and Aims: ZHX2 transcriptional factor is normally found in podocyte membrane forming complexes with ZHX1 and APA or ZHX3 and Ephrin B1. Altered ZHX2 expression disrupts these interactions and is related with the worsening of different primary glomerular diseases such as focal segmental glomerulosclerosis (FSGS) and minimal change disease (MCD). A small percentage of Hodgkin lymphoma (HL) patients develop nephrotic syndrome (NS). Studies of Reed-Sternberg cell line L-1236 reveals a chromosomal rearrangement that leads to ZHX2 downregulation suggesting a possible role of ZHX2 in the development of NS in these patients. Human podocyte disease relapse is common after a common cold probably mediated by cytokines released by immune cells and the rhinovirus. Our aim is to study how the presence of insertions and deletions (InDels) between HAS2 and ZHX2 in patients with MCD, FSGS and HL could alter ZHX2 expression and the implication in podocyte disease relapse after a common cold and in HL. Method: Genomic DNA between HAS2 and ZHX2 (Chr8:122624000-124001000 from UCSC hg19 GRCh37) was sequenced from 28 NS patients and 27 controls using Agilent Custom capture and high throughput Illumina sequencing. The CLC Genomics software was used to identify InDels (3-20 bp) present exclusively in patients. One of the identified InDels was replicated in human podocytes using CRISPR Cas9 and homology directed repair technology to study changes in ZHX2. A common cold cytokine cocktail containing IL-2, IL-4R, IL-6, IL-10, INF-γ, TNF-α and ICAM-1 was injected into control (BALB/c, n=5) and ZHX2 deficient mice (BALB/cJ, n=5) (Dose X); podocyte specific ZHX2 deficient (ZHX2 flox/flox cre +/+, n=3) and floxed control mice (ZHX2 flox/flox, n=3) (dose X/15). Buffalo Mna (B. Mna) rats were also injected with the cytokine cocktail (X/50) to study relapse in FSGS (n=7). Cell supernatant from HL Reed Sternberg cells (L-1236) (200µg of total protein) was injected into BALB/c (n=5) and BALB/cJ mice (n=5) and kidney function was assessed. Results: Multiple InDels were found exclusively in the patient population, two of them, shared by two or more patients. The insertion at 122, 533, 694 was presented in patients with MCD, FSGS and HL with NS and also in L-1236 cells. This insertion was replicated in human podocytes using CRISPR/Cas9 (CRISPR B). Another insertion noted both in patients and controls was generated for comparison (CRISPR A). A reduced ZHX2 expression was detected in CRISPR B but not in CRISPR A single cell clones. The shared insertion at 122, 787, 088 was presented within the ZHX2 gene intron 1. BALB/cJ mice has lower ZHX2 expression in liver and podocytes due to an insertion in intron 1. To study whether this insertion could be related with relapse of MCD and FSGS following a common cold, a cytokine cocktail was injected into BALB/cJ and BALB/c mice. BALB/cJ mice developed acute albuminuria after cytokine treatment (65.3±24.3 μg per 18h), but not control BALB/c mice (10.8±1.5 μg per 18h), when compared with baseline values (BALB/cJ 5.1±1.1 μg per 18h; BALB/c 6.5±1.1 μg per 18h) (p<0.05). BALB/cJ mice had also higher nuclear expression of ZHX1. The cytokine cocktail also induced albuminuria in ZHX2 flox/flox/cre +/+ mice but not in control ZHX2 flox/flox, suggesting that ZHX2 deficiency in podocytes is responsible of kidney injury after cytokine injection. To study common cold related relapse in FSGS, B. Mna rats were injected with a rat cytokine cocktail, showing a significant increase in proteinuria (61.5±4.2 mg per 18h) compared with baseline (47±4.1 mg per 18h). Cell culture supernatant from L-1236 was injected into BALB/cJ and BALB/c mice to study the effect of secreted soluble mediators in NS. L-1236 supernatant (200 µg) had a nephrogenic effect in ZHX2 deficient mice but not in controls. Conclusion: InDels between HAS2 and ZHX2 genes presented in patients with MCD, FSGS and HL, alter ZHX2 expression and are related to relapse following a common cold and in HL.